studi penggunaan pewarna kopigmentasi biji kesumba keling (Bixa orellana L.) Dan Angkak Merah Dalam Formulasi Suspensi Parasetamol - Salman Salman; Sudewi Sudewi; Jazilul Amira; Meutia Indriana (Journal of Pharmaceutical and Sciences, 2023)
Background; Annatto seeds (Bixa orellana L.) is a plant originating from the Americas, which is widely cultivated in tropical and subtropical areas. Red yeast rice is white rice that has undergone a fermentation process from rice and mold (Monascus purpereus). This study aims to determine the copigmentation of annatto seeds (Bixa orellana L.) and red yeast rice in the form of ethanol extract that can be formulated as a dye into paracetamol suspension which at certain concentrations can produce colors that meet the requirements and are able to provide color stability. Methods; His study used an experimental method, using the test material of annatto seeds (Bixa orellana L.) and red yeast rice with a ratio of 1:2 using maceration method using 96% ethanol solvent, formulated into paracetamol suspension preparations with concentrations of 0.25%, 0.50% , 0.75%, as well as blanks. Examination of the physical quality of the preparation includes, organoleptic examination, determination of the pH of the preparation, observation of the stability of the preparation against storage, and viscosity test. Result; The results showed that the seeds of annatto seeds (Bixa orellana L.) and red yeast in the form of ethanol extract could be formulated as a dye into the preparation of paracetamol suspension. Copigmented paracetamol suspension preparations of ethanol extract of annatto seeds (Bixa orellana L.) seeds and red yeast rice with a ratio of 1:2 are stable preparations and have a pH range of 4.1-4.4 and pH after cycling test 4.0-4.3 . Has a different color for each concentration contained with a viscosity of 102.0-136.0 dPa.s. The preparation of paracetamol suspension of formula I with a concentration of 0.25% produces a red color (+), the preparation of formula II with a concentration of 0.50% produces a red color (++), the preparation of formula III with a concentration of 0.75% produces a red color (++ +) and white blank preparations.